Prediction of mechanical properties of Polyethylene parts produced by different moulding methods - Godinho, J. S. (2002)
The properties of moulded plastic products are dependent on the processing technology used in their manufacture and in particular on the structural morphology resulting from the thermomechanical environment experienced by the melt. This paper presents a unified approach to predict the mechanical properties of the moulded parts. A linear medium density polyethylene (LMDPE) was processed using injection moulding, rotational moulding and compression moulding in order to induce different thermomechanical conditions (i.e. shear rates and cooling rates). Two models were then developed to predict the mechanical properties of the parts produced by the quite different moulding methods. One model is based on laminate theory, in which the mechanical properties of the individual layers through the wall thickness are used to predict the tensile and flexural properties of the full thickness moulding. The other approach is more generic in that it predicts the properties as a function of two thermomechanical indices. A good agreement is achieved between the experimental data and the values predicted by the models. It is also shown that the combined use of the thermomechanical indices concept and the laminate analysis permits good predictions to be made for the mechanical properties of plastic mouldings with complex microstructures. It is proposed that this approach could provide a very valuable addition to existing melt flow simulation packages. This would provide a valuable tool for designers in that not only would it be possible to optimise processing conditions, but also the properties of the end product could be predicted.